Metabolic equivalent of task (MET) scores avoid the ceiling effect observed with conventional patient reported outcome scores following knee arthroplasty - Patel,A; Edwards,T; Jones,G; Liddle,A; Cobb,J; Garner,A (Bone & Joint Open, 2023)
Aims : The metabolic equivalent of task (MET) score examines patient performance in relation toenergy expenditure before and after knee arthroplasty. This study assesses it’s use in a kneearthroplasty population in comparison with the widely used Oxford Knee Score (OKS) and EuroQol5d Index (EQ-5D) which are reported to be limited by ceiling effects.Method: One-hundred and sixteen patients with OKS, EQ-5D and MET scores before, and at least sixmonths following unilateral primary knee arthroplasty were identified from a database. Procedureswere performed by a single surgeon between 2014 & 2019 consecutively. Scores were analysed fornormality, skewness, kurtosis and the presence of ceiling/floor effects. Concurrent validity betweenthe MET score, OKS and EQ-5D was assessed using Spearman’s rank.Results: Post-operatively the OKS and EQ-5D demonstrated negative skews in distribution, with highkurtosis at six months and one year. The OKS demonstrated a ceiling effect at one year (15.7%) postoperatively. The EQ-5D demonstrated a ceiling effect at six months (30.2%) and one year (39.8%)post-operatively. The MET score did not demonstrate a skewed distribution or ceiling effect either atsix months or one year post-operatively. Weak-moderate correlations were noted between the METscore and conventional scores at six-months and one-year post-operatively.Conclusion: In contrast to the OKS and EQ-5D, the MET score was normally distributed postoperatively with no ceiling effect. It is worth consideration as an arthroplasty outcome measure,particularly for patients with high expectations.